Lime requirements and soil base saturation. - Cavalcanti, Francisco José de Albuquerque (Pesquisa Agropecuaria Brasileira, 2014)
By the results obtained from soil samples of the Zona da Mata region in Pernambuco State, Brazil, correlations between pH values and base saturation were established. Such results provided a wide range of values for base saturation: -8.59 to 88.29%, for pH (H 20): -4.0 to 6.5, and finally, for pH (CaCl 2 0.01M): between 3.5 to 6.1. The linear regression equations derived from the adjusted data associated to the proposal changes in one of the recommended procedures for lime requirements allowed the estimate of the amount of CaCO3 necessary for a given base saturation value, taking into account only the pH and the sum of bases.